Criteria for autorship of a scientific work - Petroianu, Andy (Brazilian Journal of Sexually Transmitted Diseases, 2012)
Introduction: during the development of a scientific research, one of the main difficulties is to choose the authors of the paper from all participants of the investigation. The organization of the authorship, based on the contribution of each investigator is still more complex. Objective: to propose a justified indicator for the authorship of a scientific paper. Methods: the author investigated the main research centers in Brazil in order to know their philosophy related to the authorship of a research. An assessment of the literature completed this study. Results: we present and justify the order of each investigator in the authorship or acknowledgment of the paper, based on his or her participation in the investigation. Conclusion: the investigator deserves to be included as an author of a scientific paper only if he or she has an intellectual participation in the work and also effectively contributed with the execution and accomplishment of the research.